Building and applying the measure of abstinence from the practice of scouting activities among the teachers of physical education at Baghdad Education Directorate / Rusafa2 - Sabri Mohammed Ali, Khansaa; Sami Elias, Lamia (International Journal of Psychosocial Rehabilitation, 2020)
Sports activities are considered the basis of the exchange of experience, knowledge, and reduction of routines, highlighting talent and expanding awareness, and are also an effective means of training for life to achieve proper social adjustment as well as building an integrated personality by acquiring many skills. The scouting activity is an important aspect of the preparation of the integrated personality of the individual, in which there are types of interaction that achieve for the individual many benefits associated with social and mental aspects and integration into society. This is the problem of this research. The researchers wanted to know the reasons for teachers' reluctance to actively participate in scouting activities and to stand up to problems that help to exacerbate this phenomenon in order to reach solutions. The objectives of the research are: Building and applying the measure of reluctance to practice scouting activities in the research sample. Recognition of the extent to which the scout activities were not used in the research sample. Identification of differences in the absence of scout activities in both sexes